COMMERCIAL TRAWL FISHERIES OFF KAKINADA DURING 1967-70 - Muthu, M S; Narasimham, K A; Rao, G Sudhakara; Sastry, Y Appanna; Ramalingam, P (Indian Journal of Fisheries, 2011)
OS Kakinada, both exploratory and experimental trawling by the Centraland State government organisations were in progress since 1960. But the commercialexploitation of the resources by the industry with small-sized trawlersbegan only in 1964. Since then, there is a continuous growth over the years bothin the number and size oi the trawlers. In view of the importance of detailedknowledge about tiie various aspects of a growing fishery, the relevant particularscollected during 1967-70 are presented in this article